Evaluación de la severidad de antracnosis (Colletotrichum lindemuthianum) en el cultivo de frejol (Phaseolus vulgaris L.) var. cuarentón bajo el efecto de la aplicación de silicio - Conforme Anzules, Nicole Andreina (2021)
Bean anthracnose caused by the fungus Colletotrichum lindemuthianum is one of the diseases that affects almost all bean producing areas in the world. The research work was carried out in the locality of Mocache in the Experimental Farm "La María", of the State Technical University of Quevedo located at Km. 7 of the Quevedo - El Empalme road. The general objective of this research was to evaluate the severity of anthracnose (Colletotrichum lindemuthianum) in bush bean (Phaseolus vulgaris L.) quarantine variety under the effect of silicon application. The quarantine bean variety was used in a randomized complete block design with seven treatments and three replications. The fertilizer used in the trial was SILMAG Silicium 32% (SiO2) with two applications at 15 days after sowing (dds) and at 45 dds. Severity was evaluated using visual scales and an image processor. Among the variables evaluated were anthracnose severity, yield and economic benefit/cost analysis of each treatment. To validate the program, a correlation analysis was performed and for the rest of the variables the Tukey test at 95% was applied to identify statistical differences between treatments. The results obtained show that the Leaf Doctor application is a very useful tool for measuring and evaluating the severity of the anthracnose disease with a correlation of R2= 0.75-0.97 (leaves and pods) with the visual evaluation scale. In addition, sampling for anthracnose evaluation can be done at different plant heights as there is no statistical difference. In reference to yield no treatment shows statistical difference and no treatment is more profitable, in the B/C analysis the control is superior with a value of 1 while of the other treatments that carry silicon the T3 outperforms the others with a value of 0.77. Keywords: Fertilization, phytosanitary management, LeafDoctor, phytopathogen